Partitioning evapotranspiration in an intact forested watershed in southern China. Issue 6 (6th October 2014) - Liu, Xiaodong; Li, Yuelin; Chen, Xiuzhi; Zhou, Guoyi; Cheng, Jing; Zhang, Deqiang; Meng, Ze; Zhang, Qianmei
Abstract: Accurate estimates and partition of evapotranspiration (ET) are difficult but critical for understanding terrestrial ecosystem processes and primary productivity. A multi‐year, multi‐technique study including the catchment water balance (12 years), a semi‐empirical ET model (9 years), eddy covariance (9 years), canopy water balance (1 year) and sap flow (1 year) techniques was conducted to measure ET and its components within an intact forested watershed in the subtropical region of southern China. Over a 9‐year period, the estimates of annual ET using the catchment water balance, eddy covariance and semi‐empirical ET model techniques were in close agreement, averaging 809.9 ± 62.8, 803.8 ± 36.6 and 801.6 ± 46.9 mm per year, respectively, amounting to an average of approximately 50.2% of the mean annual precipitation. Qualitative similarities in seasonal and diurnal variation were observed between the sap flow and eddy covariance estimates of water flux. Sap flow estimates of transpiration were approximately 60.2% of the annual ET estimated with the eddy covariance technique. Interception evaporation was 31.7% of the total ET and was demonstrated to be a main contributor of total evaporation. Soil evaporation was calculated to be approximately 8.1% of the total annual ET and 4.7% of the annual precipitation. Furthermore, daytime transpiration exhibited a logarithmic increase with increases in the vapour pressure deficit (VPD) on daily scale in both the wet and dry seasons, and tended to level off when the VPD was >1 kPa because of the stomatal regulation of transpiration. Correspondingly, nighttime sap flow amounted to an average of approximately 6% of the total daily sap flow, and no significant correlations with the VPD, air temperature or relative humidity were found. Essential differences among the mechanisms of evaporation and transpiration were demonstrated, suggesting that soil evaporation is primarily a climate‐driven process, with air temperature and wind speed as the predominant driving forces. Copyright © 2014 John Wiley & Sons, Ltd.